TEACHING LISTENING COMPREHENSION THROUGH PODCASTS AND AUDIOBOOKS - Rasulova S.U; Temirova Hulkar. N (TADQIQOTLAR, 2025)
Abstract: Listening comprehension plays a crucial role in the process of language acquisition, yet it remains one of the most challenging skills for learners to master. Traditional classroom methods often rely on scripted dialogues or repetitive drills that fail to reflect real-life communication. With the rise of digital media, podcasts and audiobooks have emerged as effective tools to enhance listening comprehension through authentic, engaging, and context-rich audio content. This article explores how podcasts and audiobooks can be used in language classrooms to improve students’ listening skills. It examines theoretical perspectives, pedagogical approaches, and classroom practices supported by empirical evidence. The findings demonstrate that integrating podcasts and audiobooks into instruction enhances learners’ exposure to authentic language, improves pronunciation and vocabulary retention, and fosters independent and lifelong learning.